Cancer stem cell phosphatases - Momeny Majid; Arsiola Tiina; Westermarck Jukka (PORTLAND PRESS LTD, 2025)
Cancer stem cells (CSCs) are involved in the initiation and progression of human malignancies by enabling cancer tissue self-renewal capacity and constituting the therapy-resistant population of tumor cells. However, despite the exhausting characterization of CSC genetics, epigenetics, and kinase signaling, eradication of CSCs remains an unattainable goal in most human malignancies. While phosphatases contribute equally with kinases to cellular phosphoregulation, our understanding of phosphatases in CSCs lags severely behind our knowledge about other CSC signaling mechanisms. Many cancer-relevant phosphatases have recently become druggable, indicating that further understanding of the CSC phosphatases might provide novel therapeutic opportunities. This review summarizes the current knowledge about fundamental, but yet poorly understood involvement of phosphatases in the regulation of major CSC signaling pathways. We also review the functional roles of phosphatases in CSC self-renewal, cancer progression, and therapy resistance; focusing particularly on hematological cancers and glioblastoma. We further discuss the small molecule targeting of CSC phosphatases and their therapeutic potential in cancer combination therapies.